2015
DOI: 10.1002/mus.24305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of joint position on synergistic muscle activity after fatigue of a single muscle head

Abstract: Synergistic muscles compensate for the fatigued muscle in the flexed position but not in the extended position. Compensation mechanisms seem to depend on joint position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…M-wave amplitudes of the stimulated muscles decreased by À19.8% (SOL), À17.4% (GL) and À35.3% (GM). This is in line with previous studies which also found decreased M-wave amplitudes after high frequency stimulation similar to that used in the present study (Badier, Guillot, Danger, Tagliarini, & Jammes, 1999;Stutzig & Siebert, 2015). The M-wave amplitude decreased due to failure of action potential propagation on the sarcolemma (Bigland-Ritchie, 1984).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…M-wave amplitudes of the stimulated muscles decreased by À19.8% (SOL), À17.4% (GL) and À35.3% (GM). This is in line with previous studies which also found decreased M-wave amplitudes after high frequency stimulation similar to that used in the present study (Badier, Guillot, Danger, Tagliarini, & Jammes, 1999;Stutzig & Siebert, 2015). The M-wave amplitude decreased due to failure of action potential propagation on the sarcolemma (Bigland-Ritchie, 1984).…”
Section: Discussionsupporting
confidence: 94%
“…1A and F) were determined and averaged for pre-fatigue and post-fatigue test, separately. Although, torque was measured, we use the term force compensation in the discussion according to the previous literature (Stutzig & Siebert, 2015). The VAL was calculated from the MVCs with superimposed doublets and potentiated doublets ( Fig.…”
Section: Mechanical Datamentioning
confidence: 99%
See 3 more Smart Citations